Development of New Electrophiles in Palladium/Norbornene-Catalyzed ortho-Functionalization of Aryl Halides - Zhao, Kun; Ding, Linlin; Gu, Zhenhua (Synlett, 2019)
This account focuses on our work in palladium/norbornene-catalyzed selective ortho-arylation and ortho-acylation of aryl halides. It will discuss our synthetic plan, initial design and revised strategy in the enantioselective synthesis of the rhazinal family of natural products. It also shows our efforts on the α-acylation reaction by the cleavage of various C(O)–X bonds, along with some mechanistic studies.1 Introduction2 Synthesis of the Rhazinal Family of Natural Products2.1 Initial Design2.2 Revised Strategy2.3 Enantioselective Synthesis of the Rhazinal Family of Natural Products3 Catalytic ortho-Acylation3.1 Acid Chloride and Anhydride Strategy3.2 Cleavage of C(O)–S Bond of Thioesters by Pd, Norbornene and Copper Cocatalysis4 Decarboxylative Alkynylation5 Conclusion
Keywords: palladium; norbornene; cocatalysis; acylation; C–H functionalization